A study to assess knowledge and acceptability of foetal surgery for spina bifida amongst healthcare professionals in the UK. (18th May 2020) - Sacco, Adalina; Ahmed, Shahanaz; Deprest, Jan; David, Anna L.
Abstract: Foetal surgery to repair open spina bifida before birth improves infant motor function and reduces ventriculoperitoneal shunt requirement. Alongside the development of the first UK foetal surgery service, we surveyed the knowledge and acceptability of this treatment to healthcare professionals in the UK and Ireland via an electronic questionnaire. Ninety-eight (98) responses were received: MFM clinicians (21), midwives (20), paediatric neurosurgeons (17), obstetricians (15), neonatologists (13), theatre nurses (11) and commissioners (1). Overall 70% of responders agreed with the concept that foetal surgery improved neonatal outcome in selected cases; although, only 41% of paediatric neurosurgeons agreed. A variety of concerns were expressed, the most common being the lack information regarding mid- to long-term effects on the child and mother. In offering this new service, it is important that we are cognisant of healthcare professional concerns and address them by applying internationally accepted criteria for foetal surgery, emphasising patient choice and collecting long-term data. Impact statement: What is already known on this subject? Foetal surgery is a potentially controversial intervention, which is increasing in availability globally. Foetal surgery is now available in the UK on a charitable-funding basis. Prior to starting a UK foetal surgery service, we assessed the attitudes and knowledge of healthcare professionals in the UK towards this new surgery. What the results of this study add? Overall the majority of healthcare professionals agree with the concept that foetal surgery improves neonatal outcome in selected cases, but a variety of concerns exist, the most common being the lack of information regarding mid- to long-term effects on the child and mother. Other concerns included a lack of education, training and research; the specific risk of preterm birth following surgery; the evidence base for this procedure; effects on maternal choice and financial implications. What the implications are of these findings for clinical practice and/or further research? Those developing this new service should be mindful of the concerns expressed and address them by applying internationally accepted criteria for foetal surgery, emphasising patient choice and collecting long-term data.